Chatbot for education - Lu, Bryan We Zhern (Nanyang Technological University, 2025)
This project focuses on the development and implementation of an AI-powered chatbot web application tailored for educational purposes. The chatbot web application was designed to assist students and educators by providing responses to academic queries, based on learning resources, and enabling interactive sessions. Built on Large Language Models (LLMs) with a Retrieval-Augmented Generation (RAG) framework, the system was further enhanced with image processing, text-to-speech (TTS), and speech-to-text (STT) technologies. Integrated into a full-stack web application, it supports multiple user profiles tailored to different courses and topics. This report covers the system architectural design, implementation process, and presents the testing and evaluation results, highlighting its performance and suitability for educational settings.